The Tradition of Madurese Wedding Ceremony: Islamic Law and Local Tradition within the Framework of Maqāṣīd al-Sharī’a - M. Ghufron (Universitas Islam Negeri Mataram, 2018)
This study explores the encounters of Islamic law and local culture in the wedding ceremony in the villages on Madura, which have been influenced by the former kingdom in the eastern part of the island. This tradition for the village community members is so pivotal that ignoring it is tantamount to inviting calamity. This study applies the theory of Maqāṣīd al-Sharī’a and liminality of life-cycle by Arnold van Gennep. The ceremony includes several steps, starting from the parade of the groom with his envoy into the bride’s house up to the blessing to the newly married couple. Focusing primarily on two precessions in the wedding ceremony, namely ngiddhe 'tellor sampek bhesa (stemping the eggs until they break) and mengghar bhalabhar (opening rope), this study reveals that these processions mark a new phase in the life-cycle of the couple and entails symbols of meaning. Through the ceremony, the couple experiences separation and inclusion into a new chapter in their life. Because the tradition realizes happiness and fortune and dispells evil for both the couples and their exended family in general, it implies that the tradition also aims to implement the highest objective and principles of Islamic law.